miR-125b Functions as a Key Mediator for Snail-induced Stem Cell Propagation and Chemoresistance - Liu, Zixing (American Society for Biochemistry and Molecular Biology, 2013)
Chemoresistance is a major obstacle in cancer treatment. Our previous studies have shown that miR-125b plays an important role in chemoresistance. Here we report a novel mechanism that up-regulation of miR-125b through Wnt signaling by Snail enriches cancer stem cells. Overexpression of Snail dramatically increases the expression of miR-125b through the Snail-activated Wnt/β-catenin/TCF4 axis. Snail confers chemoresistance by repressing Bak1 through up-regulation of miR-125b. Restoring the expression of Bak1 or depleting miR-125b re-sensitizes Snail-expressing cancer cells to Taxol, indicating that miR-125b is critical in Snail-induced chemoresistance. Moreover, overexpression of miR-125b significantly increases the cancer stem cell population (CD24-CD44+), while depletion of miR-125b or rescue of the expression of Bak1 increases the non-stem cell population (CD24+CD44+) in Snail-overexpressing cells. These findings strongly support that miR-125b functions as a key mediator in Snail-induced cancer stem cell enrichment and chemoresistance. This novel mechanism for Snail-induced stem cell propagation and chemoresistance may have important implications in the development of strategies for overcoming cancer cell resistance to chemotherapy.